Bretschneider (Custodiol®) and St. Thomas 2 Cardioplegia Solution in Mitral Valve Repair via Anterolateral Right Thoracotomy: A Propensity-Modelled Comparison - Constantin Mork; Luca Koechlin; Thibault Schaeffer; Lena Schoemig; Urs Zenklusen; Brigitta Gahl; Oliver Reuthebuch; Friedrich S. Eckstein; Martin T. R. Grapow (Mediators of Inflammation)
Background. Single-dose cardioplegia is preferred in minimal invasive mitral valve surgery to maintain the adjustment of the operative site without change of preset visualization. The aim of our study was to compare two widely used crystalloid cardioplegias Bretschneider (Custodiol®) versus St. Thomas 2 in patients who underwent mitral valve repair via small anterolateral right thoracotomy. Material and Methods. From May 2012 until February 2019, 184 isolated mitral valve procedures for mitral valve repair via anterolateral right thoracotomy were performed using Bretschneider (Custodiol®) cardioplegia (n=123) or St. Thomas (n=61). Primary efficacy endpoint was peak postoperative high-sensitivity cardiac troponin (hs-cTnT) during hospitalization. Secondary endpoints were peak creatine kinase-muscle brain type (CK-MB) and creatine kinase (CK) as well as safety outcomes. We used inverse probability of treatment weighting (IPTW) in order to adjust for confounding by indication. Results. Peak hs-cTnT was higher after use of Bretschneider (Custodiol®) (geometric mean 716 mg/L, 95% confidence interval (CI) 605-847 mg/L) vs. St. Thomas 2 (561 mg/L, CI 467-674 mg/L, p=0.047). Peak CK-MB (geometric mean after Bretschneider (Custodiol®): 40 μg/L, CI 35-46, St. Thomas 2: 33 μg/L, CI 27-41, p=0.295) and CK (geometric mean after Bretschneider (Custodiol®): 1370 U/L, CI 1222-1536, St. Thomas 2: 1152 U/L, CI 972-1366, p=0.037) showed the same pattern. We did not see any difference with respect to postoperative complications between treatment groups after IPTW. Conclusion. Use of St. Thomas 2 cardioplegia was associated with lower postoperative peak levels of all cardiac markers that reflect cardiac ischemia such as hs-cTnT, CK, and CK-MB as compared to Bretschneider (Custodiol®) in propensity-weighted treatment groups.